(untitled) (Circe de clásicos y modernos, 2020)
The aim of this paper is to consider the epilogue (vv. 151-162) of the Virgilian cento Hippodamia –which narrates in 162 lines the myth of the princess– based on the narrative consequences of using different tenses, since this section is the only case in the whole cento where perfect tense exceeds present tense. The hypothesis is that the centonarius has ‘narrative’ motives for the use of each of those tenses, thus he can give more or less dramatic tension according to his needs.